The Effect of Adolescents' Internet Addiction on Smartphone Addiction. Issue 4 (October 2017) - Ayar, Dijle; Bektas, Murat; Bektas, Ilknur; Akdeniz Kudubes, Asli; Selekoglu Ok, Yasemin; Sal Altan, Sema; Celik, Isa
Abstract : Objective: The purpose of this study was to evaluate the effect of adolescents' Internet addiction levels on smartphone addiction. Methods: This study included 609 students from three high schools that are located in western Turkey. Numbers, percentages, and averages were used to evaluate the sociodemographic data. The Kolmogorov–Smirnov and Shapiro–Wilk tests were used to determine whether the data had a normal distribution. Results: The average age of the participants was 12.3 ± 0.9 years. Of them, 52.3% were male, and 42.8% were 10th graders. All participants had smartphones, and 89.4% of them connected to the Internet continuously with their smartphones. The study found that there was a statistically significant correlation between Internet addiction and smartphone addiction. Originality and Value: It was determined that male adolescents with high levels of Internet addiction also had high smartphone addiction levels. On the other hand, sociodemographic variables had no statistically significant effect on smartphone addiction. A number of studies in the relevant literature examined the effects of Internet addiction on adolescents' smartphone addiction. However, findings of this study are unique because they are specific to the Turkish culture, and there is a limited database in Turkey regarding this issue. The researchers believe that the findings of this study will be beneficial to show the importance of the issue in the international arena and to guide further studies to prevent this addiction because there is no reliable database about smartphone addiction in Turkey.